DISIPLIN KERJA APARATUR PEMERINTAH BAPPEDA DAERAH ISTIMEWA YOGYAKARTA - Rosidah Rosidah (LPPM UNY, 2001)
Abstract The research of the apparatus discipline aims at knowing the level of the discipline as well as the dominant factor which influent it, by taking the case in Bappeda DIY. With the existence of the research, it is expected that it can give a recommendation in the plan of human resource for the sake of improving the continuous development. The approach of this research is by using the qualitative descriptive method. According to qualitative analysis, it is discovered that the government apparatus in Bappeda of Yogyakarta showed a high responsibility, and high commitment in achieving the organization purpose. On the other hand, there seems to be a gap between the work volume and the amount of employees that make the task for each employee apparently less than it should be. It is discovered that among the factors of ability and skill, the work description, personality, and punishment, that the most dominant tendency in influencing the work discipline is the factor of personality. Therefore, in order to make the work discipline optimal, thus the alternative offered is related to the personality that is applying tha values. Those values are being open, honestly, equality, wisdom, and accountability. Keywords: discipline, apparatus